Digitalisasi Bisnis Dalam Islam : Determinasi Keputusan Pembelian Ulang Pengguna Market Place Shopee di Jawa Tengah - Arif Afendi; Maltuf Fitri; Shovia Indah Firdiyanti (Jurnal Ilmiah Ekonomi Islam, 2022)
The purpose of this research is to test and analyze the influence of information quality, application design and service quality on user satisfaction and repurchase decisions. This research was quantitative with multiple linear regression. The data in this research was primary data with 145 marketplace shopee customers in Central Java. The sampling technique was non-probability sampling. The results show that the quality of information has a negative and not significant effect on user satisfaction. Application design and service quality have a positive and significant effect on user satisfaction. User satisfaction and service quality have a positive and significant effect on repurchase decisions. Information quality and application design have a positive and but not significant effect on repurchase decisions in the shopee marketplace. The results of the path analysis show that user satisfaction can mediate the influence between information quality, application design and service quality on repurchase decisions.